2009
DOI: 10.1017/s0950268808001799
|View full text |Cite
|
Sign up to set email alerts
|

Impact of insecticide interventions on the abundance and resistance profile of Aedes aegypti

Abstract: Insecticide-based vector control is the primary strategy for curtailing dengue transmission. We used a mathematical model of the seasonal population dynamics of the dengue mosquito vector, Aedes aegypti, both to assess the effectiveness of insecticide interventions on reducing adult mosquito abundance and to predict evolutionary trajectories of insecticide resistance. We evaluated interventions that target larvae, adults, or both. We found that larval control and adult control using ultra-low-volume insecticid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 46 publications
2
55
0
2
Order By: Relevance
“…This result corroborates the findings of Luz et al [8]. Unfortunately, such high rates of intraspecific competition also trigger the evolution of the population, which adapts to new environmental conditions, as indicated by Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This result corroborates the findings of Luz et al [8]. Unfortunately, such high rates of intraspecific competition also trigger the evolution of the population, which adapts to new environmental conditions, as indicated by Fig.…”
Section: Resultssupporting
confidence: 92%
“…This effect has already been noted by Rivero et al [7] and by Luz et al [8], who discussed the effectiveness of insecticides for vector control and showed that the insecticide affects the rate of competition. Those who survive become more resistant, which leads to specialization.…”
Section: Resultssupporting
confidence: 58%
“…We highlight, for instances, the utilization of ultra low volume (ULV) insecticide [15] combined with temephos [22], also the sterile insect technique (SIT) [7,18,21,10] as a Genetic-based Vector Control (GVC). However, in this paper we do not take the epidemiology within mosquito population, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we used a simplified version of a previously developed model (Luz et al 2009 to examine the potential impact of this increased activity level of dengue-virus-infected mosquitoes on dengue transmission dynamics. A complete description of this model is beyond the scope of this short communication and can be found in the above-mentioned references.…”
mentioning
confidence: 99%
“…Seasonality is built into the transition rates between model compartments. Weather data from Rio de Janeiro were used to parameterise the temporal pattern of the transition rates, which were mathematically defined as sinusoidal functions (Luz et al 2009). The transition rate from egg to larva (t EL ) follows the pattern for precipitation because eggs hatch in response to water.…”
mentioning
confidence: 99%